PENDIDIKAN KESEHATAN MEMPENGARUHI PERILAKU MENCUCI TANGAN YANG BENAR PADA ANAK USIA SEKOLAH DASAR DI SDN INPRES 2 KAWATUNA KOTA PALU - Hasnidar; Cahya Jalu Putra, Windu Unggun; Badariati; Singkali, Dina Palayukan; Lanimpa, Ardiansyah A (Poltekkes Kemenkes Bengkulu, 2024)
Background: Health education aims to encourage or influence individuals, groups, families, and communities to adopt healthier behaviors. Proper handwashing practices are shaped by several factors, including knowledge, attitude, and motivation. Objective: To assess the impact of health education on proper handwashing behavior among elementary school children at SD Negeri Inpres 2 Kawatuna, Palu City. Method: This study used a quantitative approach with a Quasi-Experimental Design, specifically a pretest-posttest design without a control group. The sampling technique involved a total of 17 respondents. Data was collected via questionnaires and analyzed using the paired sample T-test. Results: The study revealed that, prior to health education, 82.4% of class V and VI students at SD Negeri Inpres 2 Kawatuna displayed poor handwashing behavior. After receiving health education, 88.2% of the students demonstrated good handwashing practices. A significant effect of health education was observed, as indicated by a P value of 0.000 (P < 0.05), meaning the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted, Conclusion: There is a significant impact of health education on proper handwashing behavior in elementary school children at SD Negeri Inpres 2 Kawatuna, as demonstrated by improvements from the pre-test to the post-test. Keywords: Health Education, Proper Handwashing Behavior